Intraoperative Electronic Alerts Improve Compliance With National Quality Program Measure for Perioperative Temperature Management. (May 2020) - Lakha, Sameer; Levin, Matthew A.; Leibowitz, Andrew B.; Lin, Hung-Mo; Gal, Jonathan S.
Abstract : BACKGROUND: Reimbursement for anesthesia services has been shifting from a fee-for-service model to a value-based model that ties payment to quality metrics. The Centers for Medicare & Medicaid Service's (CMS) value-based payment program includes a quality measure for perioperative temperature management (Measure #424, Perioperative Temperature Management). Compliance may impose new challenges in clinical practice, data collection, and reporting. We investigated the impact of an electronic decision-support tool on adherence to this emerging standard. METHODS: In this retrospective observational study, perioperative temperature data were collected from cases eligible for reporting this measure to CMS from a single academic medical center before and after the implementation of an electronic decision-support tool that prompted temperature measurement and maintenance of normothermia. Proportions of measure compliance were assessed using segmented regression analysis. Proportions of intraoperative temperature measurement were also assessed, and multivariable logistic regression was performed to assess the association between patient and surgical factors and measure compliance. RESULTS: A total of 24, 755 cases eligible for reporting in 2017 were assessed, and 25, 274 cases from 2016 were included as an extended baseline. Segmented time-series regression did not show a significant baseline trend in measure compliance. Introduction of the alerts was associated with an increase in overall compliance from 84.4% (95% confidence interval [CI], 83.6%–85.2%) to 92.4% (91.4%–93.4%), and an increase in intraoperative compliance from 26.8% (25.8%–27.8%) to 71.0% (69.6%–72.4%). The association between the alerts and overall compliance was also present on multivariable analysis. CONCLUSIONS: Implementation of an intraoperative decision-support tool was associated with statistically significant improvement in the maintenance of normothermia in cases eligible for reporting to CMS. This led to improved compliance with Measure #424 and suggests that electronic alerts can help practices improve their performance and payment bonus eligibility.